2010
DOI: 10.1002/adma.201000427
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nanoparticles Based on Self‐Assembled π‐Conjugated Systems

Abstract: pi-Conjugated molecules are interesting components to prepare fluorescent nanoparticles. From the use of polymer chains that form small aggregates in water to the self-assembly of small chromophoric segments into highly ordered structures, the preparation of these materials allows to develop systems with applications as sensors or biolabels. The potential functionalization of the nanoparticles can lead to specific probing. This progress report describes the recent advances in the preparation of such emittive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
230
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(238 citation statements)
references
References 117 publications
2
230
0
3
Order By: Relevance
“…However, in the literature, examples are scarce regarding the multifunctional conjugated polymer nanoparticles (CPNs) and even less with conjugated oligomer-based nanoparticles (CONs). 22,23 Recently, Schenning et al compared the capabilities of conjugated polymer nanoparticles to selfassembled oligomer-based nanoparticles in terms of their fluorescent quantum yields, stabilities, molar absorptivity, guest-holding, and releasing. 24 They demonstrated that oligomer nanoparticles have higher fluorescent quantum yields and comparable stabilities and molar absorptivity, but they release the guest faster than the conjugated polymer nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, in the literature, examples are scarce regarding the multifunctional conjugated polymer nanoparticles (CPNs) and even less with conjugated oligomer-based nanoparticles (CONs). 22,23 Recently, Schenning et al compared the capabilities of conjugated polymer nanoparticles to selfassembled oligomer-based nanoparticles in terms of their fluorescent quantum yields, stabilities, molar absorptivity, guest-holding, and releasing. 24 They demonstrated that oligomer nanoparticles have higher fluorescent quantum yields and comparable stabilities and molar absorptivity, but they release the guest faster than the conjugated polymer nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conjugated polymer nanoparticles (CPNs) have attracted a board attention from home and abroad scholar because of their easy synthesis, less toxicity and more biocompatibility [5]. In the past few years, their preparation methods and functional modifications have been explored [6][7][8]. In this paper, novel fluorescent conjugated polymers (TEB) were synthesized by Wittig and Wittig-Horner reaction, and the average molecular weight was improved effectively by Wittig-Horner reaction.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive pioneering structural study has been performed by Lee and co-workers [108,109], using a large variation of π-conjugated oligomers. The inherent characteristics of supramolecular self-assembly may exhibit predictable advantages such as a convenient preparation process, tunable properties and multi-functionality [70]. Solution-phase self-assembly of supramolecular CPs offers a powerful alternative to the thinfilm techniques [55].…”
Section: Introductionmentioning
confidence: 99%
“…The extensively used templates include surfactant micelles and aggregates [144]. Surfactant molecules such as hexadecyltrimethylammonium bromide (CTAB) [145], sodium dodecylsulfate (SDS) [146], a triblock copolymer and (PEO) 20 -(PPO) 70 -(PEO) 20 (Pluronic P123) have been explored as soft templates, acting as the segregates for nanostructures. Other useful soft templates for the synthesis of one-dimensional nanostructures include amphiphilic molecules, copolymers [147], liquid crystals, polymer nanofibres and self-assembled monolayers, biological molecules and macromolecular self-organized structures.…”
Section: Introductionmentioning
confidence: 99%